2019
DOI: 10.1016/j.compstruct.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment and damage detection in nanomodified adhesively-bonded composite joints using inkjet-printed interdigital sensors

Abstract: In this work, the development of a planar interdigital capacitive sensor, directly onto the surface of a composite, for determining the initial quality of curing of bonded composite joints and assessing their long-term durability is presented. The sensor consisted of an interlocking comb-shaped array of silver electrodes and used to monitor the progress of cure of an adhesive resin and the subsequent damage state of the bond line in adhesively-bonded composite joints using impedance spectroscopy.The obtained r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The results indicated that the mean size decreased after the addition of the CNTs in the shell wall ( Figure 2 ). As was also observed in the literature [ 6 , 7 ], smaller microcapsules were produced after the incorporation of nanoparticles, due to the reduced number of collisions between the smaller droplets. The outer UF shell of the microcapsules with a rougher surface were thicker than those of the microcapsules with smoother surfaces.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The results indicated that the mean size decreased after the addition of the CNTs in the shell wall ( Figure 2 ). As was also observed in the literature [ 6 , 7 ], smaller microcapsules were produced after the incorporation of nanoparticles, due to the reduced number of collisions between the smaller droplets. The outer UF shell of the microcapsules with a rougher surface were thicker than those of the microcapsules with smoother surfaces.…”
Section: Resultssupporting
confidence: 74%
“…Multifunctional composites represent a state-of-the-art technology, since they are capable of simultaneously performing two or more functions [ 1 ]. Among their functionalities, such as energy harvesting [ 2 , 3 , 4 ] and structural health monitoring (SHM) [ 5 , 6 , 7 , 8 ], self-healing is being vigorously studied [ 9 , 10 ]. Self-healing can be intrinsic [ 11 , 12 , 13 , 14 ] or extrinsic, with the incorporation of vascules [ 15 ] or capsules [ 16 ] inside the material.…”
Section: Introductionmentioning
confidence: 99%
“…Aircraft SHM is one of the scenarios where great attention has been drawn, especially when composite materials are widely adopted nowadays [11]. In order to detect damage at an early stage and to prevent catastrophic failures, many monitoring methodologies using various types of sensors have been investigated, including those using strain gauges, accelerometers, ultrasonic sensors, passive acoustic sensors and fibre optical sensors [12,13,14,15,16]. Among them, piezoelectric transducers (PZTs) have been widely used, due to their advantages in structural compactness, installation convenience and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the main sensor technologies that have received attention are Piezoelectric (PZT) transducers and Fibre optic (FO) sensors due to their many advantages, either used individually [ 15 , 16 ] or in combination [ 17 , 18 , 19 , 20 , 21 , 22 ]. There are other sensor technologies for bondline monitoring which have been recently developed [ 23 , 24 , 25 ] and hence have lower maturity than PZT and FO sensors, in particular, in harsh operational environments such as aircraft structures. In a hybrid system the advantages of utilising PZTs as actuators is combined together with the advantages of the FO sensors which have high sensitivity to strain, low weight, ability to compensate temperature, possibility of multiplexing and immunity from electromagnetic interference [ 20 , 26 ].…”
Section: Introductionmentioning
confidence: 99%